Investigation of the molecular mechanism of Smilax glabra Roxb. in treating hypertension based on proteomics and bioinformatics - Yang, Xin; Qian, Haibing; Yang, Changfu; Zhang, Zhiyuan (Frontiers in Pharmacology, 2024)
Background: Smilax glabra Roxb. (named Tufuling in Chinese, SGR) has both medicinal and edible value. SGR has obvious pharmacological activity, especially in anti-inflammation and treating immune system diseases. This study investigated differential protein expression and its relationship with immune infiltration in hypertension treated with SGR using proteomics and bioinformatics. Methods: N-nitro L-arginine methyl-ester (L-NAME) was used to replicate the hypertension model, with SGR administered by gavage for 4 weeks, and the systolic and diastolic blood pressure in each group of rats was measured using the tail-cuff method every 7 days. Furthermore, an enzyme-linked immunosorbent assay (ELISA) was used to determine the serumtotal cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) expressions in each group, followed by the detection of protein expression in rat liver samples using the tandem mass tag (TMT) technique. Additionally, hub targets were output using Cytoscape3.9.1 software, and ALDH2 expression in the liver and serum in each group of rats was detected by ELISA. Moreover, R4.3.0 software was used to evaluate the relationship between acetaldehyde dehydrogenase 2 (ALDH2) and immune cells and ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) to identify the components of SGR. Furthermore, the association between components of SGR and ALDH2 was analysed with molecular docking and Ligplot1.4.5 software. Results: Compared with the model group (L-NAME), SGR at high and medium doses reduced systolic and diastolic blood pressure while reducing TC, TG and LDL-C and increasing HDL-C levels in hypertensive rates (P < 0.05). Moreover, 92 differentially expressed proteins (DEPs) were identified using TMT, and participated in peroxisome, fatty acid degradation and other signaling pathways, with ALDH2 being the core target and correlated with various immune cells. In addition, eighteen components were determined in SGR, with eight compounds binding to ALDH2. Molecular docking was performed to confirm SGR played a role in hypertension based on the combined action of multiple components. Conclusion: SGR has an antihypertensive effect on L-NAME-induced hypertension, with ALDH2 as its hub target. SGR may regulate neutrophil, regulatory T cell and other cell infiltration by targeting ALDH2, thereby contributing to the treatment of hypertension.